2009
DOI: 10.1007/s10195-008-0043-1
|View full text |Cite
|
Sign up to set email alerts
|

Learning curve in tissue sparing total hip replacement: comparison between different approaches

Abstract: BackgroundThe tissue sparing surgery (TSS) concept means not only smaller incisions but also less tissue disruption, allowing decreased blood loss and improved function. However, TSS techniques can result in more complications related to the learning curve. The aim of this study was to compare the learning curve of an experienced surgeon with different TSS approaches for total hip replacement (THR) from a clinical and surgical point of view, focussing especially on complications related to the use of different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
103
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(131 citation statements)
references
References 15 publications
7
103
0
3
Order By: Relevance
“…However, this cohort included his learning curve, suggesting that 3D planning may help decrease the intra-operative complication rate in the early experience of DAA. Indeed, with respect to the intra-operative complications, the learning curve varies according to the authors from 20 [18] to 200 [1,5]. In our future work, we will replicate this study with a variety of surgeons with different skill levels.…”
Section: Discussionmentioning
confidence: 79%
“…However, this cohort included his learning curve, suggesting that 3D planning may help decrease the intra-operative complication rate in the early experience of DAA. Indeed, with respect to the intra-operative complications, the learning curve varies according to the authors from 20 [18] to 200 [1,5]. In our future work, we will replicate this study with a variety of surgeons with different skill levels.…”
Section: Discussionmentioning
confidence: 79%
“…This may be the result of the perception that there is faster recovery, less pain, and potentially a reduced risk of dislocation with the anterior approach [17]. Several studies, however, have demonstrated a higher rate of complications when comparing the anterior approach to THA and have suggested that this is the result of a learning curve for the technique [4,5,15,18]. Although the learning curve is usually associated with a surgeon early in his or her career, changing prostheses or approach may well result in a different outcome.…”
Section: Introductionmentioning
confidence: 99%
“…There are other complications of concern, not seen with traditional approaches, such as greater trochanter fracture, canal perforation, and remote site fractures [3,11,34,37,38]. The learning curve associated with newer approaches may also have negative implications on the results [10,28,50]. Only a few studies have specifically evaluated the impact of surgical approach on surgical outcomes including complications and short-and medium-term survivorship [2,34,39].…”
Section: Introductionmentioning
confidence: 99%